Proactive Mission of the Reference Standard Center during the COVID-19 Pandemic - หลิมศิริวงษ์ เมทินี; สหเมธาพัฒน์ อมร; กาญจนาพฤกษ์ ปิติกาญจน์; ธนสีลังกูร นวนิตย์; แช่มชมดาว ปัณรส; พ่อเสือ นนธวัฒน์; ชัยชนะ จารุบล; วิเชียรทอง รจเรข; สุรพันธุ์สกุล กัญญาภัค (Journal of Health Science of Thailand, 2025)
The Reference Standard Center of the Bureau of Drugs and Narcotics (BDN), Department of Medical Sciences, is a national and ASEAN regional agency responsible for producing reference materials (standard substances) for pharmaceuticals. These materials support the quality control of raw materials and pharmaceutical products. During the severe outbreak of COVID-19, Thailand established primary treatment guidelines using antiviral drugs such as favipiravir and molnupiravir, along with the herbal medicine Fa Thalai Chon, which contains the active compound andrographolide, for patients with mild symptoms. However, there was a shortage of COVID-19 medications, including both domestically produced and imported drugs, as well as the necessary standard substances. The objective of this study was to develop analytical methods and production techniques for these three substances in accordance with ISO 17034:2016 standards for the production of reference materials. This process involved characterizing and verifying the identity of active compounds as well as assessing their stability and homogeneity. As a result, reference standards for andrographolide, favipiravir, and molnupiravir were successfully produced, with purity values of 98.2%, 99.5% and 99.3%, respectively, calculated on an as-is basis and comparable with the primary reference standards. These locally produced reference standards play a crucial role in supporting quality control agencies in both the public and private sectors, pharmaceutical manufacturers, research institutions and academic organizations. They enable the timely development of drug formulations and quality control processes for these three medications, ensuring that patients receive the correct dose and leading to more effective treatments..